Progress of infant obesity is associated with higher aspartyl-glutamate and alanyl-aspartate in maternal and neonatal blood - Liu, Yuanying; Ma, Mingyue; Yu, Yanhong; Yang, Chunyuan; Yang, Jianling; Han, Tongyan; Wang, Yongqing (Frontiers in Public Health, 2025)
ObjectiveNeonatal obesity may be associated with the intra-uterine environment during pregnancy. The objective of this study was to evaluate the risk of neonatal obesity born from the mothers with abnormal glucose and lipid metabolism.MethodsTwenty neonates born from maternal glucose and lipid metabolism disorders and developed obesity at 6 months of age were enrolled as study group, and 20 neonates without obesity were included as control group. Non-targeted metabolomic analysis was performed in maternal serum during pregnancy and neonatal cord blood at birth to identify differential metabolites.ResultsThe concentrations of aspartyl-glutamate and alanyl-aspartate in maternal serum progressively rise steadily as gestational age advances, peaking in umbilical cord blood. Additionally, at each stage of pregnancy (early, middle, and late), the levels in both maternal serum and umbilical cord blood are significantly higher in the obese group than in the non-obese group. Their mechanisms of action may be associated with pathways involving immune-inflammatory regulation, energy metabolism, and gut microbiota modulation. Their mechanisms of action may be associated with pathways involving immune-inflammatory regulation, energy metabolism, and gut microbiota modulation.ConclusionThrough the analysis of maternal blood during pregnancy and umbilical cord blood, this study putatively identified some differential metabolites associated with neonatal obesity. In the future, it is expected that analyzing maternal blood or umbilical cord blood at birth could help predict potential infant obesity risks, enabling more dietary guidance and interventions during infancy to reduce the risk of obesity later in life.